2008
DOI: 10.1021/jm7013088
|View full text |Cite
|
Sign up to set email alerts
|

New Bis(2-aminoimidazoline) and Bisguanidine DNA Minor Groove Binders with Potent in Vivo Antitrypanosomal and Antiplasmodial Activity

Abstract: a Abbreviations: CQ = chloroquine; FACS = Fluorescence-activated cell sorting; FPIX = ferriprotoporphyrin IX; HEPES = 4-(2-hydroxyethyl)-1-piperazinethanesulfonic acid; MEM = minimum essential medium; MOA = mechanism of action; µCi = microCurie; Pip = piperidine; SI = selectivity index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
138
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(144 citation statements)
references
References 47 publications
4
138
1
1
Order By: Relevance
“…The mice that survived 60 days free of parasites were considered as cured ( Table 1). were all positive at day 7. g Data previously reported in reference [11] and shown here for comparative purpose. h Not determined.…”
Section: In Vitro and In Vivo Antiprotozoal Activitymentioning
confidence: 98%
See 4 more Smart Citations
“…The mice that survived 60 days free of parasites were considered as cured ( Table 1). were all positive at day 7. g Data previously reported in reference [11] and shown here for comparative purpose. h Not determined.…”
Section: In Vitro and In Vivo Antiprotozoal Activitymentioning
confidence: 98%
“…The choice of these scaffolds as antitrypanosomal templates was also supported by the excellent results obtained with bis (2-aminoimidazoline) analogues that proved to be 100% curative in vivo in the STIB900 mouse model [11]. (I) and 1,3-Diphenylurea (II) Bisguanidinium Leads [11] In previous work, Arafa et al [15] showed that N-alkyl derivatives of diguanidino fused ring systems had improved in vivo potency in the STIB900 mouse model of acute HAT compared with the unsubstituted diguanidino parent compounds. In the present study, we tested a similar strategy with the hits I and II to check if the antiprotozoan activity of these hits could be enhanced in that way.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations